Research on optimal dispatching method of power systems with high proportion of clean energy based on multi-energy complementarity. Issue 1 (March 2020) - Gou, Jing; Wang, Xi; Su, Yunche; Yang, Xinting; Li, Ao; Jin, Zhibo; Li, Huaqiang
Abstract: The rapid development and large-scale utilization of clean energy is not only conducive to alleviate the global fossil energy crisis, but also brings huge economic and environmental benefits. However, the uncertainty of new energy represented by wind power and photovoltaic power brings a lot of impact on the operation and dispatching of the power system. Hence, it's urgent to explore a new dispatching mode adapted to the power system with high proportion of clean energy. The optimal dispatching method of power system with high proportion clean energy based on multi-energy complementarity is explored with goal of making full use of clean energy and reducing the operating cost. Particle swarm optimization algorithm and branch and bound method are used to solve the cascade hydropower optimal dispatching problem and the wind, photovoltaic, thermal power joint optimal dispatching problem respectively. Finally, the feasibility of the model is verified by an example.